Composite positive plate, composite positive structure, all-solid-state battery cell and all-solid-state battery
By wet coating solid electrolyte on the high-load positive electrode layer prepared by dry method, combined with dry method and wet method, the electrochemical performance degradation and electrode film problems in the preparation of all solid state batteries are solved, and high energy density and suitable scale are achieved All-solid-state batteries produced in chemical production.
Patent Information
- Application Number
- CN202310869246.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-14
AI Technical Summary
During the preparation process of existing all-solid-state batteries, the wet process leads to a decrease in electrochemical performance, and the dry process has problems such as low tensile strength and uneven thickness of the electrode film, making it difficult to achieve the preparation of high energy density.
The high-load positive electrode layer prepared by dry method is uniformly coated with ultra-thin solid electrolyte slurry by wet method to form a composite positive electrode sheet. Combined with the advantages of dry method and wet method, it realizes the preparation of all-solid state battery with high energy density.
It maintains the excellent ionic conductivity of the positive electrode material, improves density and energy density, is suitable for large-scale production, solves the instability problems of PTFE and metal lithium, and achieves an energy density of about 400Wh/kg.
Smart Images

Figure CN119314985A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solid-state batteries and relates to a composite positive electrode sheet, a composite positive electrode structure, an all-solid-state battery cell and an all-solid-state battery. Background Art
[0002] Compared with traditional liquid lithium-ion batteries, all-solid-state lithium-ion batteries use solid electrolytes with good thermal stability and safety to replace traditional organic electrolytes, effectively solving the problems of poor safety performance, narrow operating temperature range and low electrochemical window in liquid batteries.
[0003] The existing preparation routes of all-solid-state batteries are mainly the following:
[0004] (1) The process of combining powder positive electrode with powder electrolyte: The powder is directly pressed into tablets using a pressurized mold to assemble a small all-solid-state powder battery. It is mainly used to assemble prototype batteries in the laboratory and evaluate materials and technical solutions. It is difficult to apply on a large scale.
[0005] (2) Wet coating process: that is, the positive electrode layer and the solid electrolyte layer are first prepared into a slurry, and then coated on the current collector to prepare a composite electrode. The advantage of this process is that it can achieve continuous and uniform coating, and can take into account the existing lithium battery production line for large-scale production. However, the solid electrolyte powder added to the positive electrode is corroded by the solvent during the wet slurrying process, resulting in a sharp decline in electrochemical performance, which seriously affects the discharge capacity of the positive electrode material. In addition, after the solvent evaporates during the drying process, more pores will be left in the positive electrode, especially for thicker positive electrode loads. The electrode has a greater impact. In general, due to the characteristics of the process, it is difficult to achieve a higher positive electrode load by wet method, and it is difficult to obtain ultra-high energy density, so it is difficult to give full play to the advantages of high energy density of all-solid-state batteries.
[0006] (3) Dry process: All processes are prepared by dry method, without using solvents, and without coating, drying, solvent recovery and other processes. Electrodes with a thickness of 30μm-3mm can be manufactured. The energy density of all-solid-state batteries prepared by dry process can be increased by 20%, but the dry process has problems such as low tensile strength of electrode film and uneven thickness of electrode sheets.
[0007] In order to give full play to the advantages of different processes, existing research has begun to focus on the application of composite processes in all-solid-state batteries. For example, patents CN114725485A and CN115360433A use a method that combines wet preparation of positive and negative electrode sheets with dry preparation of electrolyte layers, mainly to avoid the problem of serious decrease in electrolyte ion conductivity during the wet process. However, the CN114725485A method requires great pressure during the preparation process, and the thickness of the electrolyte layer cannot be controlled at a low level. Laser cutting is also required, which is difficult to operate and costly, and cannot be adapted to large-scale production. Although the powder spraying method of CN115360433A can effectively control the thickness of the electrolyte layer, the powder spraying thickness uniformity is low, and the overall operation is cumbersome. At the same time, due to the limited positive electrode load, the energy density of the all-solid-state battery cannot reach a high level. Summary of the invention
[0008] In view of the problems existing in the prior art, the present invention provides a composite positive electrode sheet, a composite positive electrode structure, an all-solid-state battery cell and an all-solid-state battery. The present invention forms a composite positive electrode sheet by uniformly coating a layer of ultra-thin solid electrolyte slurry on a high-load positive electrode layer prepared by a dry method by a wet method, which can give full play to the performance advantages of the all-solid-state battery and achieve a higher energy density.
[0009] In a first aspect, the present invention provides a composite positive electrode sheet, the composite positive electrode sheet comprising a positive electrode layer and a solid electrolyte layer coated on one side of the positive electrode layer;
[0010] The positive electrode layer is prepared by dry rolling of materials including positive electrode active materials; and the solid electrolyte layer is prepared by wet coating on one side of the positive electrode layer.
[0011] As a preferred embodiment of the present invention, the thickness of the positive electrode layer is 30 μm-500 μm.
[0012] As a preferred embodiment of the present invention, the active material loading of the positive electrode layer is ≥40 mg / cm 2 .
[0013] As a preferred embodiment of the present invention, the thickness of the solid electrolyte layer is 5-500 μm, preferably 20-60 μm.
[0014] As a preferred embodiment of the present invention, the thickness deviation of the solid electrolyte layer is ≤5 μm.
[0015] As a preferred embodiment of the present invention, the solid electrolyte in the solid electrolyte layer wet-coated on one side of the positive electrode layer includes any one of a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte or a composite solid electrolyte, or a combination of at least two thereof.
[0016] As a preferred embodiment of the present invention, the positive electrode layer comprises the following components: 30wt%-95wt% positive electrode active material, 4wt%-60wt% solid electrolyte, 0.5wt%-5wt% conductive agent, and 0.1wt%-5wt% fiberizable binder.
[0017] As a preferred embodiment of the present invention, the positive electrode active material includes any one of lithium cobalt oxide, lithium manganese oxide, spinel lithium manganese oxide, lithium-rich manganese oxide, lithium nickel cobalt aluminum oxide or lithium nickel manganese cobalt oxide, or a combination of at least two thereof.
[0018] As a preferred embodiment of the present invention, the solid electrolyte includes any one of a chloride solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte or a polymer solid electrolyte, or a combination of at least two of them.
[0019] As a preferred embodiment of the present invention, the conductive agent includes any one of graphite, Super-P, acetylene black, Ketjen black, VGCF or CNT, or a combination of at least two thereof.
[0020] As a preferred embodiment of the present invention, the fiberizable binder includes any one of PTFE, a copolymer of tetrafluoroethylene and a monomer, PVDF or PPC, or a combination of at least two thereof.
[0021] As a preferred embodiment of the present invention, the preparation of the solid electrolyte layer includes:
[0022] The solid electrolyte slurry is applied to one side of the electrode layer and then dried.
[0023] As a preferred embodiment of the present invention, the coating method includes any one of blade coating, transfer coating, extrusion coating, cast coating or micro-gravure coating, or a combination of at least two of them.
[0024] As a preferred embodiment of the present invention, the coating has a thickness of 20 μm-60 μm.
[0025] As a preferred embodiment of the present invention, the drying temperature is 40°C-150°C.
[0026] As a preferred embodiment of the present invention, the drying time is 1h-24h.
[0027] As a preferred embodiment of the present invention, the preparation of the solid electrolyte slurry comprises: dispersing the solid electrolyte and the binder in a solvent, and stirring to obtain the solid electrolyte slurry.
[0028] As a preferred embodiment of the present invention, the adhesive includes any one of PVDF, PEO, styrene-butadiene rubber, butadiene rubber, isoprene rubber, nitrile rubber, chloroprene rubber, ethylene-propylene rubber, butyl rubber, polyurethane rubber or acrylic rubber, or a combination of at least two thereof.
[0029] As a preferred embodiment of the present invention, the mass ratio of the solid electrolyte to the binder is (9-19):1.
[0030] As a preferred embodiment of the present invention, the solvent includes any one of toluene, xylene, isobutyl isobutyrate, ethyl acetate, butyl butyrate, benzyl butyrate, ethylene dichloride or heptane, or a combination of at least two thereof.
[0031] As a preferred embodiment of the present invention, the stirring rate of the stirring is 100 rpm-1000 rpm.
[0032] As a preferred embodiment of the present invention, the stirring time is 0.5h-5h.
[0033] As a preferred embodiment of the present invention, the content of the solid electrolyte in the solid electrolyte slurry is 20wt%-90wt%.
[0034] As a preferred embodiment of the present invention, the method for preparing the positive electrode layer comprises:
[0035] After the positive electrode active material, solid electrolyte and conductive agent are mixed, a fiberizable binder is added for fiberization, and the fiberized material is rolled to obtain a positive electrode layer.
[0036] As a preferred embodiment of the present invention, the mixing speed is 300 rpm-20000 rpm, and the mixing time is 0.1 h-5 h.
[0037] As a preferred embodiment of the present invention, the fiberization method includes any one of air flow pulverization, screw extrusion, high-speed stirring or differential rolling, or a combination of at least two of them.
[0038] As a preferred embodiment of the present invention, the gas pressure in the air flow milling is 0.3MPa-0.6MPa, and the feed rate is 30g / min-300g / min.
[0039] As a preferred embodiment of the present invention, the rotation speed in the high-speed stirring is 10000 r / min-20000 r / min, and the stirring time is 1-30 min.
[0040] As a preferred embodiment of the present invention, the temperature of the roller pressing is 40° C.-150° C., and the roller pressing speed is 1 m / min-15 m / min.
[0041] In a second aspect, the present invention provides a composite positive electrode structure, comprising a current collector and two of the aforementioned composite positive electrode sheets, the sides of the two composite positive electrode sheets not coated with a solid electrolyte layer facing each other, and the current collector being located between the two composite positive electrode sheets and in contact with the side of the composite positive electrode sheets not coated with a solid electrolyte layer.
[0042] In a third aspect, the present invention provides a method for preparing the aforementioned composite positive electrode structure, the method comprising: placing two composite positive electrode sheets with their sides not coated with a solid electrolyte layer facing each other, placing a current collector between the two composite positive electrode sheets, and pressing to obtain a composite positive electrode structure;
[0043] As a preferred embodiment of the present invention, the pressing pressure is 10MPa-100MPa.
[0044] In a fourth aspect, the present invention provides an all-solid-state battery cell, comprising a negative electrode sheet and the aforementioned composite positive electrode structure.
[0045] In a fourth aspect, the present invention provides an all-solid-state battery, comprising the aforementioned all-solid-state battery cell.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] (1) The positive electrode layer of the composite positive electrode sheet of the present invention is prepared by a dry method, and no solvent is used in the preparation process, thereby preventing the solid electrolyte material in the positive electrode layer from being corroded by the solvent, maintaining its excellent ionic conductivity, and thus facilitating the capacity of the positive electrode material;
[0048] (2) In the composite positive electrode sheet of the present invention, the solid electrolyte slurry is coated on the positive electrode layer by a wet method, which can fill the gaps on the surface of the positive electrode layer and further improve the density of the positive electrode layer. At the same time, the wet slurry has better wettability with the positive electrode layer and can be in close contact with the positive electrode layer after drying and rolling;
[0049] (3) In the composite positive electrode sheet of the present invention, a layer of solid electrolyte is coated on the surface of the positive electrode layer by a wet coating process (e.g., doctor blade coating), which can achieve a thinner effect than the solid electrolyte prepared by the dry method, so that the solid electrolyte layer reaches a thickness of 20 μm;
[0050] (4) The solid electrolyte in the composite positive electrode sheet of the present invention does not use polytetrafluoroethylene (PTFE) as a binder during the preparation process, which solves the problem that PTFE and metallic lithium are unstable and affect battery performance;
[0051] (5) The composite positive electrode sheet of the present invention can give full play to the performance advantages of all-solid-state batteries and achieve an energy density of about 400Wh / kg;
[0052] (6) The process proposed in the present invention can match the existing continuous automation equipment in the battery industry and is suitable for the continuous preparation of high-energy-density all-solid-state batteries, which is conducive to promoting the early large-scale production of all-solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1Schematic diagram of the structure of the composite positive electrode sheet in Example 1 of the present invention;
[0054] Figure 2 Schematic diagram of the structure of the composite positive electrode structure in Example 1 of the present invention;
[0055] Figure 3 is a charge / discharge voltage curve diagram of the all-solid-state battery in Example 1 of the present invention;
[0056] Figure 4 is a charge / discharge voltage curve diagram of the all-solid-state battery in Example 2 of the present invention;
[0057] Figure 5 is a charge / discharge voltage curve diagram of the all-solid-state battery in Example 3 of the present invention;
[0058] Figure 6 This is a charge / discharge voltage curve of the all-solid-state battery in Comparative Example 1 of the present invention;
[0059] Figure 7 This is a charge / discharge voltage curve of the all-solid-state battery in Comparative Example 2 of the present invention;
[0060] Among them, 1-positive electrode layer, 2-solid electrolyte layer, 3-double-sided carbon-coated aluminum foil current collector. DETAILED DESCRIPTION
[0061] In order to better illustrate the present invention and facilitate understanding of the technical solution of the present invention, the present invention is further described in detail below. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0062] The specific implementation mode of the present invention provides a composite positive electrode sheet, which comprises a positive electrode layer and a solid electrolyte layer coated on one side of the positive electrode layer;
[0063] The positive electrode layer is prepared by dry rolling of materials including positive electrode active materials; and the solid electrolyte layer is prepared by wet coating on one side of the positive electrode layer.
[0064] As a preferred embodiment of the present invention, the thickness of the positive electrode layer is 30μm-500μm, for example, 30μm, 50μm, 100μm, 150μm, 200μm, 250μm, 300μm, 350μm, 400μm, 450μm or 500μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] As a preferred embodiment of the present invention, the active material loading of the positive electrode layer is ≥40 mg / cm 2 , for example 40mg / cm2 、50mg / cm 2 、60mg / cm 2 、70mg / cm 2 or 80mg / cm 2 The above range is not limited to the listed values, and other values not listed within the above range are also applicable.
[0066] As a preferred embodiment of the present invention, the thickness of the solid electrolyte layer is 5μm-500μm, for example, 5μm, 10μm, 50μm, 100μm, 150μm, 200μm, 250μm, 300μm, 350μm, 400μm, 450μm or 500μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 20μm-60μm.
[0067] As a preferred embodiment of the present invention, the thickness deviation of the solid electrolyte layer is ≤5 μm, for example, 5 μm, 4 μm, 3 μm, 2 μm or 1 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] As a preferred embodiment of the present invention, the solid electrolyte in the solid electrolyte layer wet-coated on one side of the positive electrode layer includes any one of a chloride solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte or a polymer solid electrolyte, or a combination of at least two thereof.
[0069] As a preferred embodiment of the present invention, the positive electrode layer comprises the following components: 30wt%-95wt% of positive electrode active material, such as 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt% or 95wt%, etc., but not limited to the listed values, and other values not listed within the numerical range are also applicable; 4wt%-60wt% of solid electrolyte, such as 4wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt% or 60wt%, etc., but not limited to the listed values; Value, other values not listed in this numerical range are also applicable; conductive agent 0.5wt%-5wt%, for example 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%, etc., but not limited to the listed values, other values not listed in this numerical range are also applicable; fiberizable binder 0.1wt%-5wt%, for example 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%, etc., but not limited to the listed values, other values not listed in this numerical range are also applicable.
[0070] As a preferred embodiment of the present invention, the positive electrode active material includes any one of lithium cobalt oxide, lithium manganese oxide, spinel lithium manganese oxide, lithium-rich manganese oxide, lithium nickel cobalt aluminum oxide or lithium nickel manganese cobalt oxide, or a combination of at least two thereof.
[0071] As a preferred embodiment of the present invention, the solid electrolyte includes any one of a chloride solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte or a polymer solid electrolyte, or a combination of at least two of them.
[0072] Among them, the sulfide solid electrolyte may include Li 6-x PS 5-x M 1+x (M=Cl, Br, I),xLi2S-(100-x)P2S5,Li 11-x M 2-x P 1+x S 12 (M=Ge, Sn or Si), etc.; oxide solid electrolytes may exemplarily include AM2(PO4)3 (Li, Na or K occupy position A, Ge, Zr or Ti usually occupy position M), ABO3, A3B2(SiO4)3 (A=Li, Na, Ca, Mg, Fe, Mn; B=Al, Fe, Cr, Ti, Zr), LLZO, LLZTO, etc. Polymer solid electrolytes may exemplarily include polypropylene oxide (PPO), polyvinylidene chloride (PVDC), polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), etc.; chloride solid electrolytes may exemplarily include Li a MX b , M is a metal element and X is a halogen element.
[0073] As a preferred embodiment of the present invention, the conductive agent includes any one of graphite, Super-P, acetylene black, Ketjen black, VGCF or CNT or a combination of at least two thereof. The conductive agent mainly adopts conductive carbon materials commonly used in the field of lithium batteries.
[0074] As a preferred embodiment of the present invention, the fibrillable binder includes any one of PTFE, a copolymer of tetrafluoroethylene and a monomer, PVDF or PPC, or a combination of at least two of them. Among them, the copolymer of tetrafluoroethylene and a monomer exemplarily includes: a copolymer of tetrafluoroethylene monomer and one or more of acrylic acid, sulfonic acid perfluorovinyl ether, etc.
[0075] As a preferred embodiment of the present invention, the preparation of the solid electrolyte layer includes:
[0076] The solid electrolyte slurry is applied to one side of the positive electrode layer and then dried.
[0077] As a preferred embodiment of the present invention, the coating method includes any one of blade coating, transfer coating, extrusion coating, cast coating or micro-gravure coating, or a combination of at least two of them.
[0078] As a preferred embodiment of the present invention, the coating has a thickness of 20 μm-60 μm.
[0079] As a preferred embodiment of the present invention, the drying temperature is 40°C-150°C, for example, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110, 120°C, 130°C, 140°C or 150°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0080] As a preferred embodiment of the present invention, the drying time is 1h-24h, for example, 1h, 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0081] As a preferred embodiment of the present invention, the preparation of the solid electrolyte slurry comprises: dispersing the solid electrolyte and the binder in a solvent, and stirring to obtain the solid electrolyte slurry.
[0082] As a preferred embodiment of the present invention, the adhesive includes any one of PVDF, PEO, styrene-butadiene rubber, butadiene rubber, isoprene rubber, nitrile rubber, chloroprene rubber, ethylene-propylene rubber, butyl rubber, polyurethane rubber or acrylic rubber, or a combination of at least two thereof.
[0083] As a preferred embodiment of the present invention, the mass ratio of the solid electrolyte to the binder is (9-19):1, for example 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1 or 19:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0084] As a preferred embodiment of the present invention, the solvent includes any one of toluene, xylene, isobutyl isobutyrate, ethyl acetate, butyl butyrate, benzyl butyrate, ethylene dichloride or heptane, or a combination of at least two thereof.
[0085] As a preferred embodiment of the present invention, the stirring rate is 100rpm-1000rpm, for example, 100rpm, 200rpm, 400rpm, 600rpm, 800rpm or 1000rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0086] As a preferred embodiment of the present invention, the stirring time is 0.5h-5h, such as 0.5h, 1h, 2h, 3h, 4h or 5h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0087] As a preferred embodiment of the present invention, the content of solid electrolyte in the solid electrolyte slurry is 20wt%-90wt%, for example, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt% or 90wt%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0088] As a preferred embodiment of the present invention, the method for preparing the positive electrode layer comprises:
[0089] After the positive electrode active material, solid electrolyte and conductive agent are mixed, a fiberizable binder is added for fiberization, and the fiberized material is rolled to obtain a positive electrode layer.
[0090] As a preferred embodiment of the present invention, the mixing rotation speed is 300rpm-20000rpm, for example 300rpm, 500rpm, 1000rpm, 3000rpm, 5000rpm, 7000rpm, 10000rpm, 13000rpm, 15000rpm, 17000rpm or 20000rpm, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable; the mixing time is 0.1h-5h, for example 0.1h, 0.5h, 1h, 2h, 3h, 4h or 5h, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0091] As a preferred embodiment of the present invention, the fiberization method includes any one of air flow pulverization, screw extrusion, high-speed stirring or differential rolling, or a combination of at least two of them.
[0092] As a preferred embodiment of the present invention, the gas pressure in the air flow milling is 0.3MPa-0.6MPa, for example, 0.3MPa, 0.4MPa, 0.5MPa or 0.6MPa, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable; the feed rate is 30g / min-300g / min, for example, 30g / min, 50g / min, 100g / min, 150g / min, 200g / min, 250g / min or 300g / min, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0093] As a preferred embodiment of the present invention, the rotation speed in the high-speed stirring is 10000r / min-20000r / min, such as 10000r / min, 12000r / min, 14000r / min, 16000r / min, 18000r / min or 20000r / min, etc., but it is not limited to the listed values, and other values not listed in the numerical range are also applicable. The stirring time is 1min-30min, such as 1min, 5min, 10min, 15min, 20min, 25min or 30min, etc., but it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0094] As a preferred embodiment of the present invention, the temperature of the roller pressing is 40°C-150°C, such as 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable. The roller pressing speed is 1m / min-15m / min, such as 1m / min, 3m / min, 5m / min, 7m / min, 10m / min, 13m / min or 15m / min, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0095] The specific implementation method of the present invention also provides a composite positive electrode structure, which includes a current collector and two of the aforementioned composite positive electrode sheets, the sides of the two composite positive electrode sheets not coated with the solid electrolyte layer are opposite to each other, and the current collector is located between the two composite positive electrode sheets and in contact with the side of the composite positive electrode sheets not coated with the solid electrolyte layer.
[0096] The specific implementation method of the present invention also provides a method for preparing the aforementioned composite positive electrode structure, which comprises: placing two composite positive electrode sheets with their sides not coated with a solid electrolyte layer facing each other, placing a current collector between the two composite positive electrode sheets, and pressing to obtain a composite positive electrode structure.
[0097] As a preferred embodiment of the present invention, the pressing pressure is 10MPa-100MPa, such as 10MPa, 30MPa, 50MPa, 70MPa or 100MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0098] The specific implementation method of the present invention also provides an all-solid-state battery cell, which includes a negative electrode sheet and the aforementioned composite positive electrode structure.
[0099] Specifically, the method for preparing the all-solid-state battery cell includes: stacking the negative electrode sheet and the composite positive electrode structure, and then applying a pressure of 10MPa-100MPa for pressing to obtain the all-solid-state battery cell.
[0100] The negative electrode sheet in the all-solid-state battery cell can be prepared by a dry method or a wet method.
[0101] Exemplarily, the wet method for preparing the negative electrode sheet includes:
[0102] The negative electrode active material, solid electrolyte, conductive agent and binder are mixed evenly in a solvent to obtain a negative electrode slurry, which is then scraped on the surface of the negative electrode current collector. The scraping thickness is determined by capacity matching based on the surface density of the positive electrode sheet, and dried at 60°C-150°C for 0.5h-6h;
[0103] The negative electrode active material includes any one or a combination of at least two of graphite, lithium titanate, metallic lithium, silicon, silicon carbon, silicon monoxide or metallic lithium alloy, but is not limited thereto.
[0104] The solid electrolyte includes any one of a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte or a composite solid electrolyte or a combination of at least two thereof, but is not limited thereto.
[0105] The conductive agent includes one or a combination of commonly used conductive carbon materials in the lithium battery field such as graphite, Super-P, acetylene black, Ketjen black, VGCF or CNT.
[0106] The binder used in the preparation process of the negative electrode sheet includes any one of polytetrafluoroethylene, polytetrafluoroethylene, benzene rubber or nitrile rubber, or a combination of at least two of them, but is not limited thereto.
[0107] The amounts of negative electrode active material, solid electrolyte powder, conductive agent and binder: negative electrode active material 30wt%-99.9wt%, such as 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt% or 99.9wt%, etc., but are not limited to the listed values, and other values not listed within the numerical range are also applicable; solid electrolyte 0wt%-60wt%, such as 0wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt% or 60wt%, etc., However, it is not limited to the listed values, and other values not listed within the numerical range are also applicable; conductive agent 0wt%-5wt%, for example 0wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%, etc., but it is not limited to the listed values, and other values not listed within the numerical range are also applicable; binder 0.5wt%-5wt%, for example 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%, etc., but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0108] Exemplarily, the dry process for preparing the negative electrode sheet includes:
[0109] After the negative electrode active material, solid electrolyte and conductive agent are mixed, a fiberizable binder is added for fiberization, and the fiberized material is rolled to obtain a negative electrode sheet.
[0110] The composition of the negative electrode active material, solid electrolyte and conductive agent is the same as that in the wet preparation method. The fiberizable binder is the same as that in the preparation process of the positive electrode sheet.
[0111] The amounts of negative electrode active material, solid electrolyte, conductive agent and fibrillable binder: negative electrode active material 10wt%-99.9wt%, for example 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt% or 99.9wt%, etc., but are not limited to the listed values, and other values not listed within the numerical range are also applicable; solid electrolyte 0.1wt%-80wt%, for example 0.1wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt% or 80wt%, etc., but are not limited to the listed values, and the values Other unlisted values within the range are also applicable; conductive agent 0.1wt%-10wt%, for example 0.1wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable; fiberizable binder 0.5wt%-10wt%, for example 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0112] The specific implementation method of the present invention also provides an all-solid-state battery, which includes the above-mentioned all-solid-state battery cell.
[0113] Specifically, the preparation method of the all-solid-state battery includes: subjecting the all-solid-state battery cell to processes such as welding the electrode ear and vacuum packaging to obtain the all-solid-state battery. The preparation method of the all-solid-state battery is a conventional preparation method in the art and is not limited to the examples listed in the present invention.
[0114] The following are typical but non-limiting embodiments of the present invention:
[0115] Embodiment 1:
[0116] The present embodiment provides a composite positive electrode sheet, a composite positive electrode structure, an all-solid-state battery cell, and an all-solid-state battery.
[0117] The composite positive electrode sheet comprises a lithium cobalt oxide (LCO) positive electrode layer prepared by a dry process and a lithium phosphorus sulfur chloride (LPSCL) electrolyte layer coated on one side of the positive electrode layer by a wet process, and the structure is as follows: Figure 1 shown.
[0118] The preparation method of the lithium cobalt oxide (LCO) positive electrode layer is as follows: lithium cobalt oxide (LCO), lithium phosphorus sulfur chloride (LPSCL), and conductive agent VGCF are mixed in a mass ratio of 80wt% of lithium cobalt oxide (LCO), 18wt% of LPSCL, and 2wt% of VGCF, and the mixing speed is 300rpm. The mixture is mixed for 2h, and 3wt% of polytetrafluoroethylene (PTFE) is added to the obtained mixture, and the mixture is fully fiberized by high shear force at a speed of 12000rpm to obtain a fluffy flocculent mixture. The fluffy flocculent mixture is subjected to high-temperature roller pressing, the rolling temperature is 80℃, and the speed is 7m / min, to obtain a positive electrode layer with a thickness of 180μm, and the positive electrode active material is 60mg / cm 2 .
[0119] The preparation method of the lithium phosphorus sulfur chloride (LPSCL) electrolyte layer is as follows: solid electrolyte lithium phosphorus sulfur chloride (LPSCL) powder is dispersed in solvent toluene, so that the content of LPSCL in the solid electrolyte slurry is 50wt%, and then 1wt% of binder NBR is added, and stirred for 2h at a stirring rate of 500rpm to obtain a solid electrolyte slurry. The solid electrolyte slurry is coated on the a surface of the positive electrode layer, and after drying at 100°C for 12h, a composite positive electrode sheet is obtained, wherein the thickness of the lithium phosphorus sulfur chloride (LPSCL) electrolyte layer is 100μm.
[0120] The prepared composite positive electrode sheet is used to prepare a composite positive electrode structure, such as Figure 2 The preparation method is as follows: two composite positive electrode sheets are placed with one side not coated with a solid electrolyte layer facing each other, a double-sided carbon-coated aluminum foil current collector is placed between the two composite positive electrode sheets, and the two composite positive electrode sheets and the double-sided carbon-coated aluminum foil current collector are pressed together by pressing at a pressure of 30 MPa to obtain a composite positive electrode structure.
[0121] An all-solid-state battery cell is prepared using a composite positive electrode structure, and the preparation method is as follows: lithium metal is used as a negative electrode and stacked together with the composite positive electrode structure, and a pressure of 0.5 MPa is applied for pressing to obtain an all-solid-state battery cell.
[0122] An all-solid-state battery is prepared by using an all-solid-state battery cell, and the preparation method is as follows: the all-solid-state battery cell is subjected to processes such as electrode ear welding and vacuum packaging to obtain the all-solid-state battery.
[0123] The all-solid-state battery is charged and discharged at 60°C and 0.05C. The charge / discharge voltage curve is as follows: Figure 3 shown.
[0124] It can be seen that under high load, the dry-wet combined all-solid-state battery with lithium cobalt oxide as the positive electrode material can be charged and discharged normally, and the discharge capacity reaches 128mAh / g, and the battery energy density is 220.4Wh / kg.
[0125] Embodiment 2:
[0126] The present embodiment provides a composite positive electrode sheet, a composite positive electrode structure, an all-solid-state battery cell, and an all-solid-state battery.
[0127] The composite positive electrode sheet comprises a lithium nickel cobalt manganese oxide (NCM811) positive electrode layer prepared by a dry process and a lithium phosphorus sulfur chloride (LPSCL) electrolyte layer coated on one side of the positive electrode layer by a wet process.
[0128] The preparation method of the positive electrode layer of lithium cobalt nickel manganese oxide (NCM811) is as follows: lithium cobalt nickel manganese oxide (NCM811) lithium phosphorus sulfur chloride (LPSCL) and conductive agent VGCF are mixed in a mass ratio of 80wt% of lithium cobalt nickel manganese oxide (NCM811), 18wt% of LPSCL and 2wt% of VGCF, the mixing speed is 300rpm, and the mixing is carried out for 2h, 3wt% of polytetrafluoroethylene (PTFE) is added to the obtained mixture, and the mixture is fully fiberized by high shear force at a speed of 12000rpm to obtain a fluffy flocculent mixture. The fluffy flocculent mixture is subjected to high-temperature roller pressing film, the rolling temperature is 80℃, and the speed is 7m / min, to obtain a positive electrode layer with a thickness of 182μm, and the positive electrode active material is 60.8mg / cm 2 .
[0129] The preparation method of the lithium phosphorus sulfur chloride (LPSCL) electrolyte layer is the same as that in Example 1.
[0130] The preparation method of the composite positive electrode structure, the all-solid-state battery cell and the all-solid-state battery is the same as that in Example 1.
[0131] The all-solid-state battery is charged and discharged at 60°C and 0.05C. The charge / discharge voltage curve is as follows: Figure 4 shown.
[0132] It can be seen that under high load, the dry-wet combined all-solid-state battery with ternary materials as the positive electrode can also be charged and discharged normally, which not only illustrates the universality of the dry-wet combination method, but also has a discharge specific capacity of up to 182.4mAh / kg and a battery energy density of 387Wh / kg.
[0133] Embodiment 3:
[0134] The present embodiment provides a composite positive electrode sheet, a composite positive electrode structure, an all-solid-state battery cell, and an all-solid-state battery.
[0135] The preparation method of the composite positive electrode structure is the same as that in Example 2.
[0136] The preparation method of the composite electrolyte layer is as follows: solid electrolyte lithium phosphorus sulfur chloride (LPSCL) and lithium lanthanum zirconium tantalum oxide (LLZTO) powders are dispersed in solvent toluene, so that the content of lithium phosphorus sulfur chloride (LPSCL) and lithium lanthanum zirconium tantalum oxide (LLZTO) in the solid electrolyte slurry is 50wt%, and then 1wt% of binder NBR is added, and stirred for 2h at a stirring rate of 500rpm to obtain a solid electrolyte slurry. The solid electrolyte slurry is coated on the a surface of the positive electrode layer, and after drying at 120°C for 12h, a composite positive electrode sheet is obtained, wherein the thickness of the composite electrolyte layer is 200μm.
[0137] The preparation method of the all-solid-state battery is the same as that in Example 1.
[0138] The all-solid-state battery is charged and discharged at 60°C and 0.05C. The charge / discharge voltage curve is as follows: Figure 5 shown.
[0139] It can be seen that using different electrolyte systems, the dry-wet combined all-solid-state battery with ternary materials as the positive electrode can still be charged and discharged normally, which illustrates the diversity of the selection of solid electrolyte systems in the dry-wet combination method, and further illustrates the universality of the scheme described in the present invention in the field of solid-state battery preparation.
[0140] Embodiment 4:
[0141] This embodiment provides four types of composite positive electrode sheets, and corresponding composite positive electrode structures, all-solid-state battery cells, and all-solid-state batteries.
[0142] The structures and preparation methods of the four composite positive electrode sheets are the same as those in Example 2, with the only difference being that the thicknesses of the positive electrode sheets are 125 μm, 149 μm, 182 μm, and 196 μm, respectively.
[0143] The structure and preparation of the composite positive electrode structure, all-solid-state battery cell and all-solid-state battery are the same as those in Example 2.
[0144] The all-solid-state battery was electrochemically tested at 60°C and 0.05C, and the results are shown in Table 1. It can be seen that the greater the active material loading, the greater the energy density.
[0145] Table 1 Performance test table
[0146]
[0147] Comparative Example 1:
[0148] This comparative example provides a composite positive electrode structure, an all-solid-state battery cell, and an all-solid-state battery.
[0149] In the composite positive electrode structure, a lithium nickel cobalt manganese oxide (NCM811) positive electrode layer is prepared by a wet method, and a lithium phosphorus sulfur chloride (LPSCL) electrolyte layer is prepared by a wet method.
[0150] The preparation method of the composite positive electrode structure is as follows: lithium cobalt nickel manganese oxide (NCM811) lithium phosphorus sulfur chloride (LPSCL), styrene butadiene rubber (SBR), and conductive agent VGCF are mixed in a mass ratio of 80:27:1:2, and then a toluene solution is poured into it to make the solid content 60wt%, and the rotation speed is 300rpm. After 2h of mixing, a positive electrode slurry is obtained, and the positive electrode slurry is scraped and coated on both sides of the carbon-coated aluminum foil. After drying, a positive electrode structure is obtained. The thickness of the positive electrode layer on one side of the carbon-coated aluminum foil is 100μm, and the surface density is 25mg / cm 2 .
[0151] Solid electrolyte lithium phosphorus sulfur chloride (LPSCL) powder was dispersed in toluene solvent, the content of LPSCL in the solid electrolyte slurry was 50wt%, and 1wt% of binder SBR was added, stirred for 2h at a stirring rate of 500rpm to obtain solid electrolyte slurry.
[0152] The solid electrolyte slurry was coated on both sides of the positive electrode layer with a thickness of 40 μm, dried at 120° C. for 0.5 h, cut into required sizes, and rolled at a pressure of 300 MPa to obtain a composite positive electrode structure.
[0153] Metal lithium was selected as the negative electrode and the composite positive electrode structure to form an all-solid-state battery cell, and an all-solid-state battery was prepared. The charge and discharge were carried out under the conditions of 60°C and 0.05C. The charge / discharge voltage curve is shown in the figure below. Figure 6 shown.
[0154] It can be seen that the battery can be charged and discharged stably, but the initial efficiency is low, only 70.92%. Although the discharge capacity reaches 1469.6mAh, the discharge specific capacity of the NCM811 positive electrode material is only 143.2mAh / g, and the battery energy density is only 213.47Wh / kg.
[0155] The performance parameters of the all-solid-state battery composed of positive electrode layers with different loadings prepared by the wet coating process in this comparative example and metal lithium are compared (test conditions: 60°C, 0.05C), as shown in Table 2. It can be seen that all the all-solid-state batteries prepared by the wet pulping coating process can achieve normal charge and discharge when the positive electrode thickness ranges from 100μm to 250μm. With the increase of the positive electrode thickness, the gram capacity of the NCM811 positive electrode material is significantly reduced, so that when the positive electrode thickness reaches 250μm, the corresponding active material loading reaches 39.4mg / cm 2When the gram capacity of NCM811 cathode material is only 143.2mAh / g, the corresponding energy density is only 213.47Wh / kg. Therefore, the battery prepared by the full wet process has a significant disadvantage in energy density compared with the dry method for preparing the cathode and the wet method for preparing the electrolyte layer described in the present invention.
[0156] Table 2 Performance test table
[0157]
[0158] Comparative Example 2:
[0159] This comparative example provides a composite positive electrode sheet, a composite positive electrode structure, an all-solid-state battery cell, and an all-solid-state battery.
[0160] The composition and preparation method of the positive electrode layer in the composite positive electrode sheet are the same as those in Example 2. The preparation of the lithium phosphorus sulfur chloride (LPSCL) electrolyte layer is as follows: LPSCl is blended with 1wt% PTFE at a high speed, fiberized under high shear force, and a 100μm thick electrolyte membrane is prepared on one side of the positive electrode layer by rolling at a rolling temperature of 80°C and a speed of 7m / min.
[0161] The composite positive electrode structure, all-solid-state battery cell and all-solid-state battery preparation method are the same as those in Example 2. The all-solid-state battery is charged and discharged at 60°C and 0.05C, and its charge / discharge voltage curve is as shown in Figure 7 shown.
[0162] It can be seen that the all-solid-state battery prepared by the pure dry method has an increased interface resistance and a low discharge capacity due to the side reaction of PTFE and lithium at low potential; in addition, due to the high porosity in the electrolyte membrane, lithium dendrites will pierce the electrolyte layer, causing a direct short circuit in the battery.
[0163] The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A composite positive electrode sheet, characterized in that: The composite positive electrode sheet comprises a positive electrode layer and a solid electrolyte layer coated on one side of the positive electrode layer; The positive electrode layer is prepared by dry rolling of materials including positive electrode active materials; and the solid electrolyte layer is prepared by wet coating on one side of the positive electrode layer.
2. The composite positive electrode sheet according to claim 1, characterized in that: The thickness of the positive electrode layer is 30 μm-500 μm; Preferably, the active material loading of the positive electrode layer is ≥40 mg / cm 2 ; Preferably, the thickness of the solid electrolyte layer is 5 μm-500 μm, preferably 20 μm-60 μm; Preferably, the thickness deviation of the solid electrolyte layer is ≤5 μm: Preferably, the solid electrolyte in the solid electrolyte layer wet-coated on one side of the positive electrode layer includes any one of a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte or a composite solid electrolyte, or a combination of at least two thereof.
3. The composite positive electrode sheet according to claim 1, characterized in that: The positive electrode layer comprises the following components: 30wt%-95wt% of positive electrode active material, 4wt%-60wt% of solid electrolyte, 0.5wt%-5wt% of conductive agent, and 0.1wt%-5wt% of fiberizable binder; Preferably, the positive electrode active material comprises any one or a combination of at least two of lithium cobalt oxide, lithium manganese oxide, spinel lithium manganese oxide, lithium-rich manganese oxide, lithium nickel cobalt aluminum oxide or lithium nickel manganese cobalt oxide; Preferably, the solid electrolyte comprises any one of a chloride solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte or a polymer solid electrolyte, or a combination of at least two thereof; Preferably, the conductive agent comprises any one or a combination of at least two of graphite, Super-P, acetylene black, Ketjen black, VGCF or CNT; Preferably, the fiberizable binder includes any one of PTFE, a copolymer of tetrafluoroethylene and a monomer, PVDF, and PPC, or a combination of at least two of them.
4. The composite positive electrode sheet according to claim 1, characterized in that: The preparation of the solid electrolyte layer comprises: After coating the solid electrolyte slurry on one side of the positive electrode layer, drying it; Preferably, the coating method includes any one of blade coating, transfer coating, extrusion coating, cast coating or micro-gravure coating, or a combination of at least two thereof; Preferably, the coating has a thickness of 20 μm-60 μm; Preferably, the drying temperature is 40°C-150°C; Preferably, the drying time is 1h-24h.
5. The composite positive electrode sheet according to claim 4, characterized in that: The preparation of the solid electrolyte slurry comprises: dispersing the solid electrolyte and the binder in a solvent, and stirring to obtain the solid electrolyte slurry; Preferably, the adhesive comprises any one or a combination of at least two of PVDF, PEO, styrene-butadiene rubber, butadiene rubber, isoprene rubber, nitrile rubber, chloroprene rubber, ethylene-propylene rubber, butyl rubber, polyurethane rubber or acrylic rubber; Preferably, the mass ratio of the solid electrolyte to the binder is (9-19):1; Preferably, the solvent comprises any one or a combination of at least two of toluene, xylene, isobutyl isobutyrate, ethyl acetate, butyl butyrate, benzyl butyrate, ethylene dichloride or heptane; Preferably, the stirring rate of the stirring is 100rpm-1000rpm; Preferably, the stirring time of the stirring is 0.5h-5h; Preferably, the content of the solid electrolyte in the solid electrolyte slurry is 20wt%-90wt%.
6. The composite positive electrode sheet according to claim 3, characterized in that: The preparation method of the positive electrode layer comprises: The positive electrode active material, the solid electrolyte and the conductive agent are mixed, and then a fiberizable binder is added to perform fiberization, and the fiberized material is rolled to obtain a positive electrode layer; Preferably, the mixing speed is 300rpm-20000rpm, and the mixing time is 0.1h-5h; Preferably, the fiberization method includes any one of air flow milling, screw extrusion, high-speed stirring or differential rolling, or a combination of at least two thereof; Preferably, the gas pressure in the air flow milling is 0.3MPa-0.6MPa, and the feed rate is 30g / min-300g / min; Preferably, the rotation speed in the high-speed stirring is 10000r / min-20000r / min, and the stirring time is 1min-30min; Preferably, the rolling temperature is 40° C.-150° C., and the rolling speed is 1 m / min-15 m / min.
7. A composite positive electrode structure, characterized in that: The composite positive electrode structure includes a current collector and two composite positive electrode sheets according to any one of claims 1 to 6, the two composite positive electrode sheets having sides not coated with a solid electrolyte layer facing each other, and the current collector is located between the two composite positive electrode sheets and in contact with the side of the composite positive electrode sheets not coated with a solid electrolyte layer.
8. The method for preparing a composite positive electrode structure according to claim 7, characterized in that: The preparation method comprises: placing two composite positive electrode sheets with their sides not coated with a solid electrolyte layer facing each other, placing a current collector between the two composite positive electrode sheets, and pressing to obtain a composite positive electrode structure; Preferably, the pressing pressure is 10 MPa-100 MPa.
9. An all-solid-state battery cell, characterized in that: The all-solid-state battery cell comprises a negative electrode sheet and the composite positive electrode structure according to claim 7.
10. An all-solid-state battery, characterized in that: The all-solid-state battery comprises the all-solid-state battery cell according to claim 9.
Citation Information
Patent Citations
All-solid-state battery and preparation method thereof
CN114725485A
All-solid-state battery and preparation method thereof
CN115360433A